Development of Mathematical Logic Pipeline Tools (Pilogmath) for Learning Mathematical on Logic Material - Nisa, Khairun; Saputra, Eri; Mursalin, M (International Journal of Trends in Mathematics Education Research, 2023)
This development research aims to determine the feasibility of using Mathematical Logic Pipe teaching aid (Pilogmath) on mathematical logic material at SMA Negeri 1 Tanah Luas in terms of validity, practicality, and attractiveness. The development model used is the ADDIE development model which consists of the stages of analysis (analysis), design (design), development (development), implementation (implementation), evaluation (eveluation). The subjects of this research are class X SMA Negeri 1 Tanah Luas. The feasibility of learning media refers to the results of the assessment of teaching aids by experts, teachers and small group students. Feasibility can be seen from the results of the validator's assessment where all validators stated very valid, the results of the percentage of product ratings by media experts were 81% in the “Very Valid” category, the results of the percentage of product ratings by material experts were 87% in the “Very Valid” category, the results of the percentage of product assessment by the teacher were 92% in the “Very Practical” category, and the results of the percentage of product assessment by 6 small group students were 93 .6 % in the “Very Interesting” category. Based on product assessment by all validators who stated that it was very valid, the teachers assessment stated that it was very practical, and student assessment stated that it was very interesting, the Mathematical Logic Pipe teaching aid (Pilogmath) that was developed meeting the criteria of being very feasible to use for class X students of SMA Negeri 1 Tanah Luas.